Expatriate knowledge sharing, replacement and repatriation processes in linkage with the performance management : case Metso - Itani, Sami (2011)
Along with the trend of growing interest towards expatriate assignments among MNEs, also the challenges the enterprises face have turned more complex and demand improved control of the expatriatism processes in their entirety. Particularly questions related to expatriates’ and repatriates’ knowledge sharing have arisen within the recent years and generated a need for benefiting better the differing management tools of MNEs, and additionally, awaken interests for further academic investigation. Consequently, the research objective of this study was to find out which factors are hindering expatriates’ and repatriates’ knowledge sharing at the case company Metso, and thereafter create a model that suggests organizational HR operations, which are possible to be linked in the case company’s prevailing management tools in order to enhance and standardize knowledge sharing in the selected phases of their expatriatism processes. In addition, the study aims to contribute to the prevailing expatriatism literature by combining separate articles together and, furthermore, by suggesting improvements to the Expatriate Career Cycle (ECC) model by Antal (2001). A qualitative research was conducted by applying a case study research strategy. In the study process the examined phases of expatriatism were defined by combining findings from Metso’s expatriation statistics and ECC. Afterwards, from the basis of an extensive theory overview a summary model (FISTE) of the theoretical framework was presented. Later the convenience of the FISTE model in the case company’s context was examined in the empiricism, and as a result a more practical model, named “the Metso Model”, was constructed. The empiricism consisted of four semi-structured interviews and supporting questionnaires sent to a vaster sample of case company’s expatriates. The overall findings indicate, for example, how the knowledge sharing objectives for different phases of expatriatism should be defined and presented more explicitly, and moreover, formally assigned and later evaluated together with the expatriate, his/her line manager and the company HR. Additionally, the company should provide differing channels and mechanisms to collect knowledge and it should be stored into company databases for later utilizing. Several practical and theoretical implications are suggested as well as differing paths for further research and supplements to the ECC.